Kilka uwag na temat inicjatywy „biblioteki syberyjskiej” w lwowskim Ossolineum - Michalska-Bracha, Lidia (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
Problematyka artykułu koncentruje się wokół inicjatywy zorganizowania w lwowskim Ossolineum odrębnego działu gromadzącego pamiętniki i wspomnienia dotyczące dziejów Polaków na Syberii w XIX w. Z postulatem tym wystąpił jeszcze w okresie I wojny światowej Zygmunt Librowicz (1855–1921), badacz dziejów polskiej zsyłki na Syberii, autor klasycznej już dziś monografii pt. „Polacy w Syberii” (Kraków 1884). O wyborze Ossolineum na miejsce „biblioteki syberyjskiej” zadecydowało wiele czynników: rola samego Lwowa – „opiekuna Sybiraków” w upamiętnianiu polskiej zsyłki i funkcja miasta jako znaczącego ośrodka wydawniczego pamiętników z zesłania oraz centrum badań historycznych nad dziejami polskiej zsyłki w XIX w, przede wszystkim jednak pozycja lwowskiej książnicy w dokumentowaniu polskiego dziedzictwa narodowego i polskiej kultury w dobie niewoli narodowej. Inicjatywa ta przypadła na trudny okres w dziejach lwowskiego Ossolineum. Z uwagi na brak dostatecznego potwierdzenia źródłowego trudno jest jednoznacznie stwierdzić, w jakim stopniu do pomysłu Librowicza powrócono w latach międzywojennych.

This article discusses the initiative to organize a separate department in Lviv Ossolineum gathering diaries and memoirs concerning the history of Poles in Siberia in the 19th century. This postulate was put forward during World War I by Zygmunt Librowicz (1855–1921), a researcher into the history of Polish exile in Siberia, the author of classic monograph entitled “Polacy w Syberii” (Poles in Siberia) (Krakow 1884). Many factors decided about choosing Ossolineum for the seat of the “Siberian library”, namely the role of Lviv itself as a “protector of Siberian exiles” in commemorating Polish exile and the function of the city as a significant publishing center for diaries from the exile and a center of historic studies on Polish exile in the 19th century, and most of all the position of Lviv library in documenting Polish national heritage and Polish culture at the time of annexation. This initiative happened during a difficult time in the history of Lviv Ossolineum. Due to lack of sufficient source confirmation it is difficult to state firmly to what degree Librowicz’s idea was revived in the interwar period.
Keywords: biblioteka syberyjska; dzieje Polaków na Syberii; XIX wiek; dzieje Lwowa; historia Ossolineum; Zygmunt Librowicz; Michał Janik; Siberian library; history of Poles in Siberia; 19th century; Lviv history; Ossolineum history